Analisis Kinerja Campuran Aspal Beton (AC–BC) Menggunakan Liquid Asbuton Dengan Penambahan Serpih Sampah HDPE (High Density Polyethylene) - Daud Nawir; Achmad Zultan M (Borneo Engineering : Jurnal Teknik Sipil, 2020)
The use of asphalt (Liquid asbuton) as a road pavement material can be an economical and efficient choice for road construction and maintenance because, in addition to being cheaper and having better work abilities compared to other types of buton asphalt, a new step is carried out by using Asbuton liquid in a hot mix. One of the materials used is high-density polyethylene (HDPE) plastic waste. The ideal plastic prohibition needs to be balanced with waste management and financial incentives to change the habits of consumers and industry players. This research was conducted to determine the effect of using HDPE type plastic as an addition to the Asphalt Layer mixture Concrete (Laston) in terms of Marshall characteristics by using liquid asbuton and the level of plastic addition used was 2%, 4%, and 6% The results achieved were the addition of plastic waste flakes into the asphalt concrete mixture AC-BC can save asphalt 6% to the weight of asphalt The characteristics of the AC-BC mixture can be explained that with the addition of plastic waste flakes, stability will rise, flow decreases, Marshal Quotien (MQ) increases, VIM decreases, VMA decreases, VFB increases with increasing levels of effective asphalt, remaining marshall stability can be reached above 90%, and the cavity in the cam Puran at the refusal density can be achieved in the range greater than 2%.